THE PHASES OF INDUSTRIAL DEVELOPMENT IN SABAH - Firdausi Suffian (International Journal of Accounting, Finance and Business, 2022)
This paper is a preliminary assessment of the industrial development in Sabah. It iswidely known industrial development is the primary key to modernise an economy andstructural change. Transition of structural change requires the state to configure coherentindustrial policy to ensure industrial development can take place. Throughout the history ofSabah industrial development, the state has continuously attempted to industrialise the statebut transition to pursue structural change is limited. This limitation is due to the inefficacy ofplanning and implementation of industrial policy which is influenced by political dynamic ofthe state and federal-state relations. This paper examines phases of industrial development andpolitical dynamics of the state. Policy priority defines by elite policymaker and asymmetricalpower relations between federal and state government can likely hinder a desired trajectory ofindustrial policy outcome.